ON IMPACT INTERACTION OF FALLING WHEAT GRAIN ON RIGID CONCRETE SILO BASE - Samoilenko, T. V.; Arendarenko, V. M.; Antonets, A. V.; Koshova, O. P. (Scientific Progress & Innovations, 2021)
One of the ways to reduce grain damage is its safe loading in storage silos. Reducing the impact interaction of grain with the working bodies of machines and mechanisms is one of the indicators of the technical level of modern agricultural production. The issues of impact energy transfer, determination of force impulses, recovery and rebound coefficients at grain falling on the concrete bottom of silos have not been sufficiently studied. The purpose of the article is the theoretical study of the oblique impact of grain on the concrete silo bottom as a result of its free falling. When determining the impact force, it is necessary to take into that the grain falling on the concrete bottom has already some speed. The scheme of falling winter wheat grain interaction with a motionless hard surface has been given in the work. The moment of impact is divided into two stages. The first stage is characterized by a change in the shape and condition of the body being struck. At the second stage, the initial shape of the grain is restored due to its viscous elastic and plastic deformation. At each stage, the time and speed of grain movement were considered and analyzed. According to the conducted analysis and using Newton's second law in impulse form, the total vector momentum of the grain impact was found. Based on this, the formula for finding the maximum force of grain contact interaction with the silo concrete base at an oblique impact was presented. Using the geometric characteristics of winter wheat grain and the duration of sound wave propagation in concrete, the instantaneous impact time was determined taking into account the nominal diameter of winter wheat grain. Using Rouse’s hypothesis, the impact impulses along the corresponding coordinate axes and the recovery factor at grain’s oblique impact on the concrete base were determined. Taking into account the found total impact impulse, the dependence for determining the impact force of the grain on the silo concrete bottom at its oblique impact was obtained. It has been established that the impact value depends on the speed and height of the grain falling, as well as on the physical and mechanical properties of the silo concrete bottom and the geometric dimensions of the grain. Based on the obtained equation, the value of the impact force at the wheat grain falling to the silo bottom was calculated. It has been shown that the impact force is a function of the impact coefficient of sliding friction and at its increase the impact force also increases. This is due to the longer interaction of the grain with the silo concrete bottom, and is caused by sliding friction.